PENGARUH METODE PEMBELAJARAN RECIPROCAL DALAM MENINGKATKAN KETERAMPILAN PASSING BAWAH PERMAINAN BOLA VOLI KELAS VIII DI SMP NEGERI 1 TANAH PUTIH - Fahmi Fadillah; Aref Vai; Siti Maesaroh (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study looked at how the reciprocal learning approach helped grade VIII volleyball students at SMP Negeri 1 Tanah Putih improve their lower passing skills during the odd semester of the 2024–2025 school year. The study sought to ascertain the effect of the independent variable (treatment) on the dependent variable (outcome) under controlled circumstances by utilizing an experimental technique with quantitative methods. There were 98 pupils in total, 52 of whom were male and 46 of whom were female, in grade VIII. The sample was limited to all of the pupils in class VIII.1. The Brumbach forearms pass wall-volley test was the tool used to evaluate the fundamental lower passing abilities. The t-test with degrees of freedom (df = N-1) at a 5% significant level was used to analyze the data using the experimental approach with a pre-test and post-test design. Once it was established that the data had a normal distribution, the t-test was used to test the hypothesis. According to the results, SMP Negeri 1 Tanah Putih's lower passing volleyball skills were considerably enhanced by the reciprocal learning approach. The t-test results, which revealed p < alpha (0.001 < 0.05) in the Two-Sided Significance column, confirm this conclusion by showing that the reciprocal learning strategy significantly improves volleyball passing abilities.